MS and GC–MS Analytical Methods for On-Line Thermally Induced Evolved Gas Analysis (OLTI-EGA) - Giuseppina Gullifa; Elena Papa; Giordano Putzolu; Gaia Rizzo; Marialuisa Ruocco; Chiara Albertini; Roberta Risoluti; Stefano Materazzi (Chemosensors)
Mass spectrometry (MS) and coupled gas chromatography-mass spectrometry (GC-MS) are globally recognized as the primary techniques for the analysis of gases or vapors due to their selectivity, sensitivity, accuracy, and reproducibility. When thermal stress is applied, vapors or gases are released as a result of the reactions and changes that occur. The analysis of these gases during the thermally induced reaction is scientifically referred to as evolved gas analysis (EGA), which is essential for confirming the occurrence of the induced reactions. Pyrolyzers, thermobalances, or simple heaters can increase the temperature of the analyzed samples according to a programmed and software-managed ramp, allowing for control over both the heating rate and isothermal stages. The atmosphere can also be varied to simulate pyrolysis or thermo-oxidative processes. This way, each induced reaction generates a unique evolved gas, which can be linked to a theoretically hypothesized mechanism. Mass spectrometry (MS) and coupled gas chromatography–mass spectrometry (GC-MS) are fundamental analytical methods used for on-line thermally induced evolved gas analysis (OLTI-EGA).